2018
DOI: 10.4236/ib.2018.103008
|View full text |Cite
|
Sign up to set email alerts
|

Pricing the Cost of Cybercrime—A Financial Protection Approach

Abstract: Infrastructures, businesses, end-users and services offered in the digitally integrated environment are exposed to a wide range of risks such as denial of service, hacking, phishing, ransomware, viruses, etc. Consequently, along with their physical life, individuals and organizations have to secure their digital life as well. Digital threats may have a major economic impact both on the individuals and the society, through the direct loss of income and/or property or even an indirect reduction of the individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Beyond the immediate consequences of attacks, being exposed to cyber attacks has extensive implications on the market value of companies, as examined by Smith and Lostri (2020); Arcuri et al (2017); and Kamiya et al (2020). Estimating the actual costs is a research topic in itself, as evidenced by several papers, such as those by Dieye et al (2020); Furnell et al (2020); Poufinas and Vordonis (2018); Romanosky (2016);and The Ponemon Institute (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the immediate consequences of attacks, being exposed to cyber attacks has extensive implications on the market value of companies, as examined by Smith and Lostri (2020); Arcuri et al (2017); and Kamiya et al (2020). Estimating the actual costs is a research topic in itself, as evidenced by several papers, such as those by Dieye et al (2020); Furnell et al (2020); Poufinas and Vordonis (2018); Romanosky (2016);and The Ponemon Institute (2016).…”
Section: Introductionmentioning
confidence: 99%
“…A similar reverse approach has been put forward by Woods et al (2021), who use particle swarm optimization to derive a cyberloss distribution from cyberinsurance prices. The estimation of the actual costs is a research theme itself, as shown in several papers, e.g., by Hua and Bapna (2013); Kamiya et al (2020); Poufinas et al (2018);World Economic Forum (2015) and The Ponemon Institute ( 2016). An econometric approach relating cyberlosses to company size has been proposed by Yamada et al (2019).…”
Section: Introductionmentioning
confidence: 99%